Do news improve liquidity through improved information or visibility? Evidence from Emerging Markets. (2015)
Market microstructure models imply that informed trading reduces liquidity. We test for the effect of the frequency of new releases, as a proxy of information arrival, on liquidity in the Chilean stock market. We find that news release frequency is strongly related to improved liquidity. Those results appear for both negative a positive news days and are robust using four different measures of liquidity: bid-ask spread, Amihud measure and two versions of the Zero trading variable. We also find evidence consistent with visibility and information arrival interacting for enhancing liquidity.